Аналіз принципів створення API у хмарній інфаструктурі - Бондар, Н. О.; Колтун, Ю. М. (ХНУРЕ, 2025)
A key solution for ensuring seamless integration and interaction in cloud infrastructure is the API. APIs provide a standardized set of protocols and tools for developing, integrating, and managing software applications, enabling efficient communication between distributed services. This paper analyzes the fundamental principles of API development in cloud ecosystems, focusing on best practices for creating scalable, secure, and reliable services, and explores the advantages of API-driven architectures, including cost optimization, enhanced interoperability, and reduced development complexity. A case study of AWS API Gateway illustrates how managed API services facilitate the design, deployment, and security of cloud-based applications.
Keywords: хмарна інфаструктура; створення API